Ordering and phase separation around Ti50Al25Mo25 composition in ternary Ti–Al–Mo bcc alloys - Alonso, Paula Regina (2004)
The phase equilibria of bcc-based phases in the Ti?Al?Mo alloy system has been studied from first-principles using a combination of abinitio total energy and cluster variation method (CVM) calculations. A set of effective cluster interaction parameters has been derived fromthe total energies, already computed, of 18 binary and ternary bcc superstructures. These interaction parameters were the input for CVMcomputation of alloy thermodynamics properties. The CVM has been used to determine the bcc composition?temperature phase diagram inthe Ti?Al?Mo system and site preference for bcc-based phases. The investigation focuses its attention on the discussion about the formationof a two-phase field A2+B2 around the Ti50Al25Mo25 composition to suggest some potential directions for future research and developmentactivities on high temperature bcc based superalloys.